Revolutionary Learning Approaches are Dusted Off (Global Journal of Human-Social Science, 2021)
Why many revolutionary discoveries have been dusted and not applied. Scientists from around the world have come to similar conclusions, but conservative minds do not want to break the status quo and continue as before. If philologists, physiologists and psychologists join forces, the optimal teaching methodology will be created and we will remember and learn easiliy.
Keywords: neuroscience; mirror neurons; hearing; ethnogram; emotional stimulus; weak signals; suggestive approach